Extensive and breed-specific linkage disequilibrium in Canis familiaris - Sutter, Nathan B.; Eberle, Michael A.; Parker, Heidi G.; Pullar, Barbara J.; Kirkness, Ewen F.; Kruglyak, Leonid; Ostrander, Elaine A. (Genome Research, 2004)
The 156 breeds of registered dogs in the United States offer a unique opportunity to map genes important in disease susceptibility, morphology, and behavior. Linkage disequilibrium (LD) is of current interest for its application in whole genome association mapping, since the extent of LD determines the feasibility of such studies. We have measured LD at five genomic intervals, each 5 Mb in length and composed of five clusters of sequence variants spaced 800 kb-1.6 Mb apart. These intervals are located on canine chromosomes 1, 2, 3, 34, and 37, and none is under obvious selective pressure. Approximately 20 unrelated dogs were assayed from each of five breeds: Akita, Bernese Mountain Dog, Golden Retriever, Labrador Retriever, and Pekingese. At each genomic interval, SNPs and indels were discovered and typed by resequencing. Strikingly, LD in canines is much more extensive than in humans: D′ falls to 0.5 at 400-700 kb in Golden Retriever and Labrador Retriever, 2.4 Mb in Akita, and 3-3.2 Mb in Bernese Mountain Dog and Pekingese. LD in dog breeds is up to 100× more extensive than in humans, suggesting that a correspondingly smaller number of markers will be required for association mapping studies in dogs compared to humans. We also report low haplotype diversity within regions of high LD, with 80% of chromosomes in a breed carrying two to four haplotypes, as well as a high degree of haplotype sharing among breeds.